2012
DOI: 10.1002/pssb.201248542
|View full text |Cite
|
Sign up to set email alerts
|

First principles electronic structure of coincidence site epitaxial Ag/Si(111) interface

Abstract: Ag/Si(111) heterojunction having $25% lattice mismatch can be formed by placing four surface unit cells of Ag(111) on three surface unit cells of Si(111), thereby reducing the effective strain in the Ag film to $0.3% in this coincidence site epitaxial growth. We have carried out first-principles investigation of such Ag/Si(111) interface to establish the interplay between the structural and electronic properties. While the Ag overlayer affects the reconstruction of the Si(111) surface, we find that the geometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The trend of evolution is in reasonable agreement with the free electron model, Fig. 11 [17,18]. The change of the values of L x , L y and L z amounts to change of electron density, which affects DOS.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The trend of evolution is in reasonable agreement with the free electron model, Fig. 11 [17,18]. The change of the values of L x , L y and L z amounts to change of electron density, which affects DOS.…”
Section: Resultssupporting
confidence: 83%
“…The electronic DOS in the Ag system is influenced by the proximity of Si across the interface [18]. Also Ag induces metal induced gap (MIG) states within the band gap of Si [18]. However, our free electron model appears to agree with the observed trend in the 0-D to 2-D crossover regime.This trend is shown by the smooth line in Fig.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…It must be noted that the real value of the barrier height often deviates from the simple theoretical estimation. 25 …”
Section: Details Of Picsmentioning
confidence: 99%
“…The E b value used for the best fit, 0.87 eV, is still lower than the theoretical energy threshold (1.2–1.57 eV). It was reported that the work function of Au nanoparticles and Schottky-barrier height at the interface between a Au nanoparticle and an n-type semiconductor are smaller than those for bulk Au. , In addition, the Schottky-barrier height often deviates from the theoretical value by several hundreds of millivolts . Actually, a photopotential response was observed upon 900 nm light irradiation (ca.…”
Section: Resultsmentioning
confidence: 99%